汉语作为第二语言习得语音格局研究综述: Review Study on Sound Pattern in Mandarin as Second Language Learning - Ting, Hie Ling; S. Sunarti (ERUDITE: Journal of Chinese Studies and Education, 2022)
语音格局是一种语言系统性的表现形式，其内容包括元音格局、辅音格局、声调格局等。汉语语音格局研究最先出现在方言研究中。经学者努力钻研下，语音格局的研究扩展到汉语作为第二语言习得研究，也促成了一定的研究成果。本文通过中国学术期刊全文知网数据库（CNKI）检索2001-2021年间汉语作为第二语言习得语音格局相关的文献，最终获得81篇相关文献，并对文献的研究方法、研究对象的国别、研究内容以文献分析法进行统计分析。文献分析结果发现，汉语作为第二语言习得的语音格局研究方法包括：声学语音实验法、知觉感知实验法和综合法。文献中的主要研究对象主要来自亚洲区，然后是欧洲区、非洲区、美洲区和大洋洲区；文献主要研究内容依次排序为元音格局、声调格局和辅音格局。本文也针对统计分析结果阐述相关研究的特点以及不足之处，以作为今后研究工作的借鉴。Abstract Sound pattern is a description of speech sound which including vowels pattern, consonants pattern, tone pattern etc. Studies on sound pattern of Mandarin was first conducted on Mandarin Dialect and it has extended to the field of Second Language Acquisition (SLA). China National Knowledge Infrastructure (CNKI) database were used to retrieve articles related to sound pattern in SLA. 81 articles published from year 2001-2021 were collected and analyzed. Descriptive analysis on research methodology, selection of respondents, topics covered in the study of SLA sound pattern were carried out in this study. Findings of this study show that three research methodology were utilized in the study of SLA sound pattern which are experimental phonetics, perceptual perception and mixed method. Majority of respondents were SLA learners from Asia, it is followed by Europe, Africa, America, and Oceania. Result of this study shows studies on vowels pattern was the major scope of sample studies, it is followed by tone pattern and consonants patterns. Characteristics of the studies on sound pattern were also included in this study. Thus, findings from this study provide a great insight for future research on sound patterns.  Keywords: Mandarin, second language, sound pattern, review study, document Analysis